1995
DOI: 10.1165/ajrcmb.13.5.7576689
|View full text |Cite
|
Sign up to set email alerts
|

Functional desensitization of beta agonist responses in human lung mast cells.

Abstract: The beta adrenergic agonist isoprenaline inhibited the IgE-triggered release of the preformed mediator histamine from human lung mast cells (HLMC) in a dose-dependent fashion. After prolonged (> or = 4 h) preexposure of HLMC to isoprenaline, there was a subsequent diminution in the effectiveness of a second exposure of isoprenaline to inhibit the release of histamine from activated HLMC. This induced hyporesponsiveness to isoprenaline was both concentration and time dependent. Although maximal levels of desens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 37 publications
8
30
0
3
Order By: Relevance
“…[17][18][19] In the present study, we found that IgE-dependent histamine release from cultured human mast cells was inhibited significantly by isoproterenol, salbutamol, fenoterol, and clenbuterol and that the inhibition was apparently attenuated by prolonged treatment with the agonists. On the other hand, although forskolin, an activator of adenylate cyclase, 28,29) apparently inhibited histamine release from cultured mast cells, it did not cause an attenuation of the inhibition even after prolonged treatment for up to 240 min.…”
Section: Effects Of Pretreatment For 3 Dsupporting
confidence: 54%
See 1 more Smart Citation
“…[17][18][19] In the present study, we found that IgE-dependent histamine release from cultured human mast cells was inhibited significantly by isoproterenol, salbutamol, fenoterol, and clenbuterol and that the inhibition was apparently attenuated by prolonged treatment with the agonists. On the other hand, although forskolin, an activator of adenylate cyclase, 28,29) apparently inhibited histamine release from cultured mast cells, it did not cause an attenuation of the inhibition even after prolonged treatment for up to 240 min.…”
Section: Effects Of Pretreatment For 3 Dsupporting
confidence: 54%
“…11,13,14) On the other hand, desensitization has also been observed in the inhibition of human mast cell histamine release by b 2 -adrenoceptor agonists. [17][18][19] Chong and Peachell 18) reported that isoproterenol inhibition of histamine release from human lung mast cells is considerably more susceptible to desensitizing treatments than the isoproterenol relaxation of bronchial smooth muscle. In contrast to histamine release, however, desensitization of PGD 2 and LT release inhibition by b 2 -adrenoceptor agonists has rarely been investigated.…”
mentioning
confidence: 99%
“…The mast cell response to b 2 -agonists becomes rapidly tolerant in vitro, reflecting the low receptor density of b 2 -receptors on these cells [41,42]. In asthmatic patients, there is tolerance to the mast cell protective effect of b 2 -agonists (against adenosine and allergen), but not to the protective effect against direct bronchoconstrictors [43,44].…”
Section: Mast Cell Stabilisationmentioning
confidence: 99%
“…Adrenalin ist das wichtigste Medikament, um die pathophysiologischen Abläufe der Anaphylaxie umzukehren. Es ist am wirksamsten, wenn es innerhalb der ersten Minuten einer schweren allergischen Reaktion verabreicht wird [287, 841,842]. In der Präklinik wird Adrenalin mithilfe eines vorgefüllten Autoinjektors in einer Dosierung von 300 µg als intramuskulä-re Eigeninjektion verwendet.…”
Section: Zweitgabe Von Adrenalin Bei Anaphylaxieunclassified